KAJIAN YURIDIS TENTANG PERLINDUNGAN HAK ASASI MANUSIA DALAM KEHIDUPAN BERNEGARA DI INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA - Yang Meliana (Justici, 2021)
ABSTRACT State is element that crusial in human right enforcement, meintenance in to protet social interest. To protect human right that impelemtation by state difficult enough in impementation because state to face with actions government that to tress pass on human right, maintenance that in connectin with civil rights and political rights. So in this research that happen problem is what factors that so push protect human right, what abstruction that to face n to protect human right in state life in Indonesia and how law formation to protect human right in future. Research methods include kind data, maner tell data and process method and analisys. Data kind to include material primer law, skunder law and tertier law. Tell manner data, that use is methods document study. Process method and data analysis that use in reearch methods normative law. For research can be conclution these are factors that to push protect human right is an know ledge fae principle human right, penness issue, existence middel class. Abstruction that to face in to protect human right because less consciousness society about in important to protect human right. In to do law formation in future that important is factor philosophy, sociology, and yuridis law.